ANALYSIS OF THE EFFECT OF LAYER AND THICKNESS OF THE BASE ON THE TENSILE TEST STRENGTH OF PLA PLASTIC-BASED TRASH CAN BASES : ANALYSIS OF THE EFFECT OF LAYER AND THICKNESS OF THE BASE ON THE TENSILE TEST STRENGTH OF PLA PLASTIC-BASED TRASH CAN BASES - Raihan Raihan; Agus Harijono (Jurnal Teknik Mesin, 2025)
Finding the appropriate thickness for the trash can. Will use the 3d printer method to make specimens and carried out by experimental methods that require several specimens to be tensile tested and the planned result is to find a strong thickness by knowing what thickness and layer will be used next. This research was conducted at the workshop of the Polytechnic of the State of Malang, there needs to be an innovation where the author makes several experiments  with  a  thickness  of  3  mm,  4  mm  and  the  last  one  is  5  mm  with  a  layer combination of 0.1 mm, 0. 2 mm and 0.3 mm to find out at what thickness and using what layer we should use, When we have found the thickness and what layer we should use we can make another trash can using 3d printing, and in using 3d printing parameters we must use 100% infill, From the results of data analysis using statistical software shows that the p-value is 0.000 with α of 0.05 which means the p-value ˂ α, then H0 is rejected and H1 is accepted.